An Enhanced Lyapunov-Function Based Control Scheme for Three-Phase Grid-Tied VSI With LCL Filter - Sefa, Ibrahim; Ozdemir, Saban; Komurcugil, Hasan; Altin, Necmi (IEEE-Inst Electrical Electronics Engineers Inc, 2019)
In this paper, an enhanced Lyapunov-function based control scheme is proposed for three-phase grid-tied ICI-filtered voltage source inverters (VSIs). The grid-tied VSI is modeled in the synchronously rotating dq-frame. Motivated from the energy distribution in the system, an energy-like function (referred to as Lyapunov-function) is defined. Then, Lyapunov-function based control scheme is derived, which guarantees the global stability of the system. However, the derived Lyapunov-function based control scheme with single-loop cannot exhibit a satisfactory damping performance due to the poles located near imaginary axis. Therefore, an enhanced Lyapunov-function based control scheme is proposed by adding a second loop into the control variable. Unlike the existing control schemes where cross-coupling interaction exists between d- and q-axes actual currents, the cross coupling in the proposed control scheme is dependent on the inverter current references. The performance and validity of the proposed control scheme are verified by computer simulations and experimental results.
Keywords: Grid tied inverter; global stability; Lyapunov function; voltage source inverter